CREATING A STANDARDIZED ASSESSMENT FOR COURT ACCREDITATION - Zulfia Hanum Alfi Syahr (Jurnal Hukum dan Peradilan, 2019)
The improvement of court’s quality has been done through various efforts, one of them is an accreditation program. Before the implementation of internal accreditation policies, the courts under the Supreme Court had used ISO standards to maintain the service quality. Along with the development of judiciary innovations especially the dream toward the great judiciary, the Supreme Court has developed special accreditation standards for each judicial environment. General Court (Badilum) has implemented the Quality Assurance Accreditation (APM) programme in 7 assessment areas. Afterward, the Religious Courts (Badilag) in addition to 7 APM areas as in Badilum also applied 9 other assessment standards. Furthermore, the Military and Administration Agency (Badilmiltun) has 7 different accreditation assessment areas with Badilum and Badilag. The problem that will be examined is how to determine the ideal criteria for assessing court accreditation. Given that the ideal accreditation standard is not only improving the quality of court services but also being able to meet the needs and expectations of justice seekers, as indicated by the community satisfaction index. The court accreditation standard used today is the adoption of the International Framework of Court excellent (IFCE) and is adapted to the area of Bureaucratic Reform and the oversight function of the Supreme Court. The method of determining accreditation criteria is done by comparing court accreditation standards that have been used with the SERVQUAL model. The SERVQUAL model is an initial model that appears to measure service quality. The results of the study found that a number of court accreditation assessment standards has been represented the dimensions of service quality at SERVQUAL.